Analysis of the Utilization of Capitation Funds for the National Health Insurance Program at the Kute Panang Health Center - Muhammad Nuh; Mappeaty Nyorong; Thomson P. Nadapdap (Journal La Medihealtico, 2022)
The research objective is to analyze the utilization of capitation funds, utilization of services and utilization of operational costs of health services for the National Health Insurance program at the Kute Panang Health Center. Research uses are theoretical/scientific and practical uses. The type and design of the research used was descriptive qualitative. The data sources used are primary data and secondary data. Data collection techniques through interviews, observation and documentation. Data analysis techniques through data collection, data reduction, data presentation, conclusion drawing and clarification. data validity test is done through Triangulation and Member Check. the research stage consists of the pre-field stage, the field work stage, and the data analysis stage. 21 of 2016. and Decree of the District Head of Central Aceh No. 425/ Dinkes/2019 concerning the use of JKN capitation funds at Puskesmas. Analysis of utilization of health services (health workers and non-health workers) by 70%. Analysis of the Utilization of Health Service Operational Costs for activities inside the building, outside the building by 30%. 21 of 2016 and the Decree of the District Head of Central Aceh No. 425/ Dinkes/2019 as technical guidelines and regional policies in the use of JKN capitation funds at the Community Health Center. The utilization of capitation funds is 70% for payment of health services and 30% for other health operations.